SOSIALISASI PERLUASAN BIDANG SASARAN CORPORATE SOCIAL RESPONSIBILITY BAGI BADAN USAHA (KAJIAN PERMENSOS NO. 9 TAHUN 2020 TENTANG TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN BADAN USAHA) - Rahadian Arrijal Hafizh, (2021)
Every business entity has an obligation to carry out social and environmental responsibilities to maintain the company's image, preserve the environment, and empower the community around the company's operational areas. This activity is better known as Corporate Social Responsibility (CSR). Along with the development of the CSR concept, CSR is currently considered the core activity of a business as a form of commitment of business entities to take part in sustainable development. CSR activity programs carried out by business entities have a very significant impact on all parties involved in these activities, there is great potential if the field of CSR activities can be expanded again, therefore the Ministry of Social Affairs issued a regulation namely Minister of Social Affairs No. 9 of 2020 concerning the Social and Environmental Responsibility of Business Entities which expands the target field of CSR activities for business entities. In this study, researchers used qualitative research methods with an exploratory approach to clarify the concepts. Researchers conducted interviews with four resource persons from various parties related to the socialization of the expansion of this CSR target area, starting from representatives of the Ministry of Social Affairs, Business Entities, to people who receive CSR programs from business entities. The researcher summarizes how the socialization process is carried out by the Ministry of Social Affairs and how the understanding received by business entities as the target of the socialization and the implementation that is practised into their CSR programs so that it can have a big impact on the recipients of these CSR activities.